PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN GOOGLE JAMBOARD UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD INPRES 5/81 BAJOE - Sudarto, Sudarto; Abd. Kadir; A. Husnul Hatimah As. (Bajang Institute, 2024)
This research is a Classroom Action Research which aims to find out whether the application of the Think Pair Share Learning model assisted by Google Jamboard can or not improve the social studies learning outcomes of Grade 5th Students at SD Inpres 5/81 Bajoe. This research was carried out in two cycles and each cycle held two meetings through 4 stages, namely the planning, implementation, observation and reflection. The focus of the research is the application of the think pair share learning model assisted by Google Jamboard to improve students' social studies learning outcomes. The research subjects were 31 the students in Grade 5th of SD Inpres 5/81 Bajoe, consisting of 14 boys and 17 girls. The data collection technique used was a test technique with data collection instruments in the form of test sheets. Data were analyzed using descriptive statistical analysis. The research results showed that the percentage of students who achieved learning completeness from cycle I to cycle II was 64%. Conclusion: the application of the think pair share learning model assisted by Google Jamboard can improve the learning outcomes of social studies students in Grade 5th at SD Inpres 5/81 Bajoe